(untitled) (African Journal of Biomedical Research, 2019)
Maternal endothelial dysfunction, oxidative stress and inflammation are parts of the theories associated with preeclampsia. Larginine is the natural substrate for NO synthase and responsible for the production of NO, This study investigated the effect of L-arginine on blood pressure, oxidative stress and inflammatory markers in pregnant rats administered N-nitro-arginine methyl ester (L-NAME). Thirty-six nulliparous female Sprague-Dawley rats weighing between 150-170 g were divided into 4 groups as follows: control (normal saline), L-NAME (50mg/kg b.w. intraperitoneal injection from days 13-18 of pregnancy), L-NAME + L-arginine (50mg/kg b.w. and 1g/kg b.w. of L-arginine from days 13-18 of pregnancy) and L-arginine (1g/kg b.w. administered orally from days 13-18 of pregnancy). Fetal outcome and blood pressure were measured on day 19 of pregnancy. The placenta was homogenized for oxidative enzyme assay and serum nitric oxide metabolite (NOx), endothelial nitric oxide synthase (eNOS), tumor necrosis factor-α (TNF-α) and interleukin-10 (IL-10) levels were measured. L-arginine reduced blood pressure increase by L-NAME. It also reduced placenta malondialdehyde level and increased glutathione peroxidase level thereby countering the effects of L-NAME. It increased eNOS and NOx levels and decreased TNF-α level compared with L-NAME. L-arginine supplementation in rat pregnancy prevents increase in blood pressure by improving eNOS and NOx levels thereby reducing oxidative stress and reducing proinflamatorry actions of TNF-α.